2016
DOI: 10.14814/phy2.13048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nonselective optogenetic control of the medial septum over hippocampal oscillations: the influence of speed and implications for cognitive enhancement

Abstract: Optogenetics holds great promise for both the dissection of neural circuits and the evaluation of theories centered on the temporal organizing properties of oscillations that underpin cognition. To date, no studies have examined the efficacy of optogenetic stimulation for altering hippocampal oscillations in freely moving wild‐type rats, or how these alterations would affect performance on behavioral tasks. Here, we used an AAV virus to express ChR2 in the medial septum (MS) of wild‐type rats, and optically st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 54 publications
6
32
0
Order By: Relevance
“…2d, e). We also addressed whether the efficiency of pacing is dependent on the running speed, and found that at 10 Hz, pacing by MSA stimulation was particularly effective at rest and low running speeds, consistent with previous reports that theta can be paced optogenetically in this state [30, 34] (Supplemental fig. 2f).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…2d, e). We also addressed whether the efficiency of pacing is dependent on the running speed, and found that at 10 Hz, pacing by MSA stimulation was particularly effective at rest and low running speeds, consistent with previous reports that theta can be paced optogenetically in this state [30, 34] (Supplemental fig. 2f).…”
Section: Resultssupporting
confidence: 84%
“…Similarly, rhythmic hippocampal oscillations can also be driven by electrical stimulation of the fornix while the MSA is inactivated [31, 32] or by nonselective optical stimulation of septal cells [33, 34]. Taken together, these recordings have therefore shown that MSA stimulation can elicit theta-like oscillations in brain states when the theta rhythm is not typically observed.…”
Section: Introductionmentioning
confidence: 99%
“…Locomotion-dependent activity of MS cells, interconnected with subcortical regions, including several hypothalamic nuclei, is thought to underlie matching of theta frequency to changing running speed (Bland et al, 2006). Optogenetic stimulation of MS cells at theta frequency (without specificity for cell type) in freely moving rats affected hippocampal theta oscillations in a speed-depended dependent manner, being stronger at slower speeds (Blumberg et al, 2016).…”
Section: Subcortical Circuits Underlying the Behavioral Correlates Ofmentioning
confidence: 99%
“…It is well-established that the MS, via its projection to the hippocampus, plays a key role in learning and memory. For example, lesion of the septohippocampal pathway leads to deficits in spatial memory [16] and spatial working memory [18,43,44], whereas optogenetic activation of the MS improves Tmaze performance [45] and fear learning [46]. While the mechanism for these effects remain unclear, it is hypothesized that MS regulation of hippocampal theta may play a role [14,15].…”
Section: Cognitive Implicationsmentioning
confidence: 99%